Kepatuhan Mengkonsumsi Tablet Fe dan Status Gizi Berhubungan dengan Kejadian Anemia pada Ibu Hamil di Puskesmas Lempake Kota Samarinda - Imam Fathoni; Nurul Hasanah; Novia Fransiska Ngo (ITKES Wiyata Husada Samarinda, 2022)
Anemia is a condition when the hemoglobin level in the blood is lower than normal. Anemia can cause miscarriage, preeclampsia, prematurity, Low Birth Weight (LBW), and even death. The high prevalence of anemia in pregnant women at Lempake Public Health Center Samarinda is a serious problem that must be addressed immediately. This research aims to investigate the correlation between risk factors, i.e., the adherence to consuming Fe tablets and nutritional status with anemia in pregnant women at Lempake Public Health Center Samarinda. This research used analytical observational method with cross-sectional approach. The data were gathered from a list of questions and Maternal and Child Health handbook (Kesehatan Ibu dan Anak – KIA) of the pregnant women at Lempake Public Health Center Samarinda using purposive sampling method. The samples of this research were pregnant women that fulfilled the inclusion and exclusion criteria. The statistical analysis was performed using Chi-Square Test. Results of this research show 41 samples were selected, consisting of 17 pregnant women in the second trimester of pregnancy and 24 pregnant women in the third trimester of pregnancy. The result of Chi-Square test for adherence to consuming Fe tablets and Fisher test for nutritional status show p-value in succession is <0,001 and 0,028. The result showed that there was a correlation between the adherence to consuming Fe tablets and nutritional status with anemia in pregnant women.